Inovasi Pembelajaran Pendidikan Agama Islam dalam Menanggapi Tantangan Pendidikan Inklusi di Sekolah Dasar - Jamila, Isnaini Fauzia; Umam, Mochammad Mushoddakul; Rizal, Moh. Ahsan Shohifur (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
This research aims to determine various Islamic Religious Education learning models that can be implemented in inclusive education in elementary schools. This research is based on researchers’ findings that not all elementary schools know and understand the implementation of Islamic religious education for inclusive students and its objectives. This research was conducted to provide innovation to Islamic religious education teachers in implementing learning for inclusive students in elementary schools. This research was conducted using a qualitative literature study method, in which researchers collected data from various library data sources. The results of this research are that Islamic religious education for inclusive students in elementary schools is important to understand and pay attention to. The implementation of Islamic religious education for inclusive students in elementary schools can use various learning models, namely: differential learning, team collaboration learning, the use of technology in inclusive education. and project-based character learning. These various models are considered to have effectiveness and efficiency values if implemented with inclusive students in elementary schools. The study contributes to the discourse on inclusive education by providing actionable insights and adaptable teaching practices for IRE, relevant to educators and policymakers.